Audio–visual and olfactory–visual integration in healthy participants and subjects with autism spectrum disorder. Issue 15 (13th July 2019) - Stickel, Susanne; Weismann, Pauline; Kellermann, Thilo; Regenbogen, Christina; Habel, Ute; Freiherr, Jessica; Chechko, Natalya
Abstract: The human capacity to integrate sensory signals has been investigated with respect to different sensory modalities. A common denominator of the neural network underlying the integration of sensory clues has yet to be identified. Additionally, brain imaging data from patients with autism spectrum disorder (ASD) do not cover disparities in neuronal sensory processing. In this fMRI study, we compared the underlying neural networks of both olfactory–visual and auditory–visual integration in patients with ASD and a group of matched healthy participants. The aim was to disentangle sensory‐specific networks so as to derive a potential (amodal) common source of multisensory integration (MSI) and to investigate differences in brain networks with sensory processing in individuals with ASD. In both groups, similar neural networks were found to be involved in the olfactory–visual and auditory–visual integration processes, including the primary visual cortex, the inferior parietal sulcus (IPS), and the medial and inferior frontal cortices. Amygdala activation was observed specifically during olfactory–visual integration, with superior temporal activation having been seen during auditory–visual integration. A dynamic causal modeling analysis revealed a nonlinear top‐down IPS modulation of the connection between the respective primary sensory regions in both experimental conditions and in both groups. Thus, we demonstrate that MSI has shared neural sources across olfactory–visual and audio–visual stimulation in patients and controls. The enhanced recruitment of the IPS to modulate changes between areas is relevant to sensory perception. Our results also indicate that, with respect to MSI processing, adults with ASD do not significantly differ from their healthy counterparts.